Do Corporate Governance, Sustainability Reporting, and Gender Diversity Have a Financial Performance Impact? Evidence Indonesia and Malaysia Bank - Sanulika, Aris; Hidayati, Wahyu Nurul (KEUNIS, 2025)
Many studies state that governance and sustainability affect financial performance, and transparent disclosure is considered capable of increasing stakeholder trust in corporate responsibility towards the environment, however, some researchers assume that governance and sustainability reports do not have a positive impact on financial performance and are considered only a burden and only to comply with regulations. This study attempts to fill this gap in the literature by testing the impact of governance disclosure and sustainability reporting by adding gender diversity variables as a moderation, female directors are believed to be more critical and able to increase stakeholder trust. This study uses a panel regression model on a sample of 54 banks registered in Indonesia and Malaysia in 2022. Effective governance can overcome the agency theory and moral hazard problems that commonly occur in the banking industry, such that bank performance, as measured by Tobin's q, increases because stakeholders feel that greater disclosure of governance can have a positive effect on financial performance. Disclosure of sustainability reporting in the banking industry not only complies with regulations but also has a positive effect on financial performance. Sustainability reporting integration into core business strategies is likely to play an important role in driving long-term financial success and increasing stakeholder confidence in bank performance. Gender diversity positively moderates corporate governance practices, sustainability reporting, and, ultimately, superior financial performance. Gender diversity in the ranks of company directors is an important factor in improving corporate governance, sustainability reporting practices, and financial performance. The benefits of gender diversity extend to various organizational dimensions, underscoring its significance as a strategic asset in the contemporary corporate governance paradigm.